2019
DOI: 10.2478/hukin-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lower Body and Abdominal Strength in Professional Soccer Players

Abstract: The purpose of this study was to evaluate abdominal strength in professional soccer players and compare the findings to their lower body strength. An observational design was used to examine abdominal and lower body strength using two functional performance tests (a lower body isokinetic test and an isometric abdominal test, respectively). One hundred and thirty-two professional male soccer players from Cyprus’s first and second divisions participated in this study. Testing included three and twenty-five maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In a study comparing anthropometric and body composition variables between players from the Serbian premier league and the fifth Serbian league, the authors found that elite players were significantly heavier and had a lower BF% than non-elite players [26]. However, in line with our findings, another study conducted on 132 male professional soccer players found that there were no significant differences in height, body mass, and BF% between players from Division 1 and Division 2 [27], even though players from Division 1 were taller, heavier, and presented a lower BF% than players from Division 2. It is essential to clarify that BF% has been negatively correlated with physical development test performance in previous research [2,28,29], especially for tests which require full-body movement such as vertical jumping, sprinting, and change of direction.…”
Section: Discussionsupporting
confidence: 83%
“…In a study comparing anthropometric and body composition variables between players from the Serbian premier league and the fifth Serbian league, the authors found that elite players were significantly heavier and had a lower BF% than non-elite players [26]. However, in line with our findings, another study conducted on 132 male professional soccer players found that there were no significant differences in height, body mass, and BF% between players from Division 1 and Division 2 [27], even though players from Division 1 were taller, heavier, and presented a lower BF% than players from Division 2. It is essential to clarify that BF% has been negatively correlated with physical development test performance in previous research [2,28,29], especially for tests which require full-body movement such as vertical jumping, sprinting, and change of direction.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, these muscles are active in the acceleration phase of the golf swing with the highest level of activity observed in the trail-side abdominal oblique muscles ( Watkins et al, 1996 ). However, abdominal strength measured by an isometric abdominal test does not depend on playing position and/or the sports level in professional soccer players ( Michaelides et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sepak bola dianggap menuntut fisik olahraga yang memerlukan unsur dasar kekuatan dan daya tahan otot pada saat menguasai bola (Michaelides et al, 2019). Untuk menjamin kestabilan tulang anggota gerak bagian atas, otot harus memiliki kekuatan dan daya tahan yang sesuai dengan durasi pada permainan sepak bola.…”
Section: Pendahuluanunclassified